New nomenclatural combinations in Nitrosalsola (Chenopodiaceae) - Feodorova, T.A. (Український ботанічний журнал, 2015)
Thirty-two new nomenclatural combinations are validated in the genus Nitrosalsola Tzvelev (Chenopodiaceae). The genus, as newly outlined, contains both annual and perennial (shrubs and subshrubs) species earlier treated in some infrageneric groups of Salsola L. s. l., or recently transferred to Caroxylon Thunb. The new circumscription of Nitrosalsola, its morphological characters, and the need for its segregation from Caroxylon are briefly discussed